T‐cell differentiation stage block bias confers hypermethylation and mediastinal preference in T‐cell lymphoblastic lymphoma - Jiali Wang; Bo Qian; Xiaowen Yu; Yidan Zhang; Chunlei Zhou; Tingting Yang; Le Xia; Gang Zhang; Yi‐Xuan Zhang; Yaping Wang; Yongjun Fang (Clinical and Translational Medicine)
Abstract Background The clinical guideline classifies T‐LBL and T‐ALL jointly, differentiating them merely by the bone marrow blast cell proportion. However, their distinct clinical manifestations, genetic profiles, and specific pathogenic requirements have prompted us to reevaluate the differences between them. Methods and Results We established the NCH‐TALL‐LBL cohort, which includes flow cytometry data and somatic mutation data from our center. Additionally, we collected T‐LBL samples and implemented single‐cell RNA sequencing and single‐cell T‐cell receptor sequencing. Combining the single‐cell RNA sequencing data of T‐ALL, expression array data, flow cytometry data, we discovered that malignant T cells in T‐LBL are predominantly in the DN‐ and DP‐stage blocking modes (DP cells dominate). This block mode in T‐LBL generates signals that drive the development of an immunosuppressive microenvironment and the mediastinum preference. Additionally, E2F2, an active transcription factor in the DP and DN stages, upregulates the expression of UHRF1, resulting in hypermethylation of tumor suppressor genes. Findings from in vivo and in vitro research clearly show that demethylation therapy targeting this mechanism effectively inhibits tumor proliferation in T‐LBL. Conclusion From the perspective of differentiation blockage, T‐LBL and T‐ALL represent different stages of the same disease, and the stage block bias of T‐cell contributes to their heterogeneity. Key points Malignant T cells in T‐LBL are primarily blocked in the DN and DP stages, which contributes to the immunosuppressive TME and mediastinum preference of T‐LBL. The active transcription factor E2F2 in the DP and DN stages upregulates UHRF1 expression, leading to the hypermethylation of tumor suppressor genes in T‐LBL. Demethylation therapy targeting the hypermethylation of tumor suppressor genes mediated by UHRF1 effectively inhibits tumor proliferation in T‐LBL.